DEVELOPMENT AND PHYSICOCHEMICAL EVALUATION OF ANTIOXIDANT PEEL-OFF MASKS CONTAINING ETHANOL EXTRACT OF CURRY LEAVES - Sirait, Tri Susanti; Fachrunniza, Yunda; Silitonga, Desni Rinanda; Karo-Karo, Sry Ulina; Limbong, Yulia Safitri (Lantanida Journal, 2026)
Curry leaves (Bergera koenigii) are widely recognized for their rich phytochemical content and antioxidant properties; however, their application as active ingredients in cosmetic delivery systems remains relatively underexplored. This study aimed to evaluate the phytochemical profile and antioxidant activity of the ethanol extract of B. koenigii leaves and to investigate its potential incorporation into a peel-off mask formulation through physicochemical characterization. Antioxidant activity was assessed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay, while formulation quality was evaluated through organoleptic properties, homogeneity, pH, viscosity, spreadability, drying time, stability testing for 28 days, cycling test, and skin irritation assessment. Phytochemical screening confirmed the presence of tannins, flavonoids, steroids, and saponins. The ethanol extract exhibited very strong antioxidant activity with an  value of 8.23 µg/mL, indicating a high free radical scavenging capacity. The formulated peel-off masks demonstrated stable physicochemical properties during storage, with viscosity values of 6,740–13,729 cPs, spreadability of 5.3–6.6 cm, drying time of 14.03–16.36 minutes, and pH values within the acceptable skin-compatible range (6.40–6.63). No irritation responses were observed in the preliminary skin test. These findings highlight the potential of B. koenigii ethanol extract as a promising natural antioxidant ingredient for peel-off mask cosmetic formulations.